1998
DOI: 10.2307/2411308
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Versus Relative Measurements of Sexual Selection: Assessing the Contributions of Ultrasonic Signal Characters to Mate Attraction in Lesser Wax Moths, Achroia grisella (Lepidoptera: Pyralidae)

Abstract: When females choose a mate among a group of signaling males concentrated in a small area, a male's mating success is often determined not only by his absolute attractiveness but by the attractiveness of his neighbors as well. Multivariate analyses of sexual selection measurements based on absolute values of predictor variables are then misleading, because such analyses assume that the fitness of a given individual is not influenced by others. We addressed this problem of relative fitness in sexual selection by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 27 publications
2
73
2
Order By: Relevance
“…Perhaps the most important and readily tested assumption is that of relative preferences for mates (Zuk et al 1990;Hoikkala & Aspi 1993;Jang & Green® eld 1998). In some lek systems, one or a small number of males sometimes gain most of the matings.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most important and readily tested assumption is that of relative preferences for mates (Zuk et al 1990;Hoikkala & Aspi 1993;Jang & Green® eld 1998). In some lek systems, one or a small number of males sometimes gain most of the matings.…”
Section: Discussionmentioning
confidence: 99%
“…Several other univariate studies (e.g., Ryan and Keddy-Hector 1992;Polakow et al 1995;Ritchie 1996;Murphy and Gerhardt 2000) indicate that preferences for intermediate values of call frequency and various temporal structure measures may likewise result in stabilizing selection on these properties. However, analyses need to account for the simultaneous effects of selection on all relevant aspects of the phenotype (Jang and Greenfield 1998;Ryan and Rand 2003), particularly when there are genetic or phenotypic correlations among traits. The components of call structure are often phenotypically correlated in grasshoppers (Klappert and Reinhold 2003), field crickets (Scheuber et al 2003;J.…”
Section: Stabilizing Sexual Selection On Male Acoustic Signalsmentioning
confidence: 99%
“…Although tests for nonlinear sexual selection in a range of taxa have applied multivariate methods (Jang and Greenfield 1998;Blows et al , 2004Ryan and Rand 2003), none of these studies have found clear evidence of multivariate stabilizing selection. Ryan and Rand (2003) constructed artificial calls to explore the relationship between call properties and fitness in the Tú ngara frog (Physalemus pustulosus) unconstrained by phenotypic correlations among call properties.…”
Section: Stabilizing Sexual Selection On Male Acoustic Traitsmentioning
confidence: 99%
“…Playback experiments in which females were attracted to loudspeaker broadcasts of digitized song recordings indicate that phonotaxis thresholds may be as low as 50-60dBSPL [peak amplitude (Brandt et al, 2005) and unpublished data]. Studies of several A. grisella populations showed that females prefer male songs with pulses of greater peak amplitude that are delivered at a faster rhythm, and that include longer asynchrony intervals within the pulse pairs (Jang and Greenfield, 1996;Jang and Greenfield, 1998). A major portion of female evaluation of male song may be based on acoustic power, defined here as the product of mean peak amplitude and pulse pair rate: playback experiments using synthetic signals suggested that females were equally attracted to songs with low peak amplitude pulses delivered at a rapid pulse pair rate and to songs with high peak amplitude pulses delivered at a slow pulse pair rate, with acoustic power held constant in both songs (Greig and Greenfield, 2004).…”
Section: Introductionmentioning
confidence: 99%